Legal protection of business doors in the concept of business to business through electronic transactions - Nona Faradiba (Central Research Institute for Agriculture (CeRIA), 2021)
Internet media as part of information technology has shown its role in various aspects of life, including as a means of conducting business transactions. E-commerce is a modern business that changes conventional/traditional transaction methods into transactions with non-face, non-sign, paperless and borderless characteristics. Trade through e-commerce transactions has its own advantages, therefore the Government should immediately complete the consumer protection law which regulates legal protection for business actors in e-commerce transactions, so that consumers and business actors have a balanced bargaining position. The purpose of this research is to find out the mechanism in the business to business concept, legal relations to business actors in business to business, and legal protection for business actors in business to business. The research conducted is normative legal research with a normative juridical legal approach using secondary data that processes data from primary legal materials, secondary legal materials and tertiary legal materials. Based on the research results it is understood that E-commerce can provide benefits for business people because by creating an online sales site, sellers can easily meet their consumers, even consumers often come by themselves. In this legal relationship there are rights and obligations of each party. Like transactions in general, the implementation of e-commerce involves two parties including sellers and buyers, each of the transaction actors has rights and obligations that must be carried out with full awareness.